Penerapan Metode Topsis Dalam Penentuan Penerima Dana Bantuan Masyarakat Usaha Mikro Kecil Menengah - Muhamad Ibrohim; Agung Fasambi; Maya Selvia Lauryn (ProTekInfo(Pengembangan Riset dan Observasi Teknik Informatika), 2023)
The government sector, especially the village office, is obliged to convey information and serve in terms of government assistance,both cash and other direct assistance to the community. So that the village office must have a service information system in providing assistance to the community. This research was proposed to determine the beneficiaries of community assistance funds for micro, small and medium enterprises. This research process required a method to solve the system using the TOPSIS method (Technique for Orders Preference by Similarity to Ideal Solution) which is a multi-criteria decision-making method that uses the principle that the selected alternative must have the shortest distance to the positive ideal solution and the farthest distance to negative ideal solution. The steps used in the TOPSIS method are the normalization matrix calculation process, the weighted normalization matrix calculation process, the process of determining positive ideal solutions and negative ideal solutions, the process of calculating the distance between each alternative to the ideal solution, and the process of calculatingthe preference value of each alternative. The result of the calculation process of the TOPSIS method is in the form of information on the selection of beneficiaries of community assistance funds for micro, small and medium enterprises